A convenient hatred : the history of antisemitism - Goldstein, Phyllis (Facing History and Ourselves, 2012)
A Convenient Hatred chronicles a very particular hatred through powerful stories that allow readers to see themselves in the tarnished mirror of history. It raises important questions about the consequences of our assumptions and beliefs and the ways we, as individuals and as members of a society, make distinctions between "us" and "them," right and wrong, good and evil. These questions are both universal and particular